Pengaruh Kualitas Pembiayaan Murabahah terhadap Kepuasan Nasabah pada Bank Syariah Indonesia Kcp. Watampone - Kaswia Kaswia; Muhammad Yamin; Rina Novianty (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of murabahah financing quality on customer satisfaction at Bank Syariah Indonesia Sub-Branch Office (KCP) Watampone. The background of this research is based on the importance of the quality of financing services in increasing customer satisfaction as an indicator of the success of Islamic banking. The method used is a quantitative approach with a survey research type. The research sample amounted to 100 respondents who were selected using the nonprobability sampling technique using the stratified random sampling method. The research instrument was in the form of a questionnaire that was distributed directly to the respondents, and the data was analyzed using classical assumption tests, statistical tests, and hypothesis tests with the help of SPSS software. The results of the study show that the quality of murabahah financing has a positive and significant effect on customer satisfaction, with a contribution of 80.8%. These findings show that the quality of murabahah financing is the dominant factor in determining the level of customer satisfaction. This research provides a theoretical contribution to the development of Islamic banking literature, as well as practical implications for the management of Bank Syariah Indonesia to prioritize improving the quality of murabahah financing as the main strategy in building customer loyalty and achieving competitive advantage. Recommendations are given for banks to continue to improve aspects of transparency, process ease, and service in murabahah financing to increase customer satisfaction and trust.